2012
DOI: 10.1016/j.mad.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosol, a main phenol present in extra virgin olive oil, increases lifespan and stress resistance in Caenorhabditis elegans

Abstract: Extra virgin olive oil (EVOO) consumption has been traditionally related to a higher longevity in the human population. EVOO effects on health are often attributed to its unique mixture of phenolic compounds with tyrosol and hydroxityrosol being the most biologically active. Although these compounds have been extensively studied in terms of their antioxidant potential and its role in different pathologies, their actual connection with longevity remains unexplored. This study utilized the nematode Caenorhabditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 61 publications
3
62
0
1
Order By: Relevance
“…From this perspective, it would be of special interest to examine the fractions containing the polysaccharides, polyphenols, and flavonoids, as compounds belonging to these chemical classes have already been shown to possess geroprotective activities. Examples include myricetin found in many edible plants, 23 tyrosol, 24 and secoiridoid polyphenols 25 from olive oil, and the whole-apple extracts that are enriched in flavonoids. 26 The above compounds or extracts increased the resistance to stress and extended life span in the nematode Caenorhabditis elegans [24][25][26] or exhibited anti-cancer activity and prevented induction of cellular senescence.…”
Section: Geroprotective Activities Of Medicinal Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…From this perspective, it would be of special interest to examine the fractions containing the polysaccharides, polyphenols, and flavonoids, as compounds belonging to these chemical classes have already been shown to possess geroprotective activities. Examples include myricetin found in many edible plants, 23 tyrosol, 24 and secoiridoid polyphenols 25 from olive oil, and the whole-apple extracts that are enriched in flavonoids. 26 The above compounds or extracts increased the resistance to stress and extended life span in the nematode Caenorhabditis elegans [24][25][26] or exhibited anti-cancer activity and prevented induction of cellular senescence.…”
Section: Geroprotective Activities Of Medicinal Plantsmentioning
confidence: 99%
“…Examples include myricetin found in many edible plants, 23 tyrosol, 24 and secoiridoid polyphenols 25 from olive oil, and the whole-apple extracts that are enriched in flavonoids. 26 The above compounds or extracts increased the resistance to stress and extended life span in the nematode Caenorhabditis elegans [24][25][26] or exhibited anti-cancer activity and prevented induction of cellular senescence. 26 With regard to the reported data and on the basis of results obtained in this study, the Judean plants warrant further experimental investigation for their geroprotective activity.…”
Section: Geroprotective Activities Of Medicinal Plantsmentioning
confidence: 99%
“…HT and TY, the simple phenolic compounds found in olive oil, were also shown to exhibit various pharmacological health benefits. They have been reported to inhibit oxidative stress induced by various toxic chemicals and improvising the antioxidant defense system by modulating several signaling pathways (Canuelo et al, 2012;Martin et al, 2011). Previous study in our lab showed the protective potential of olive oil against Benzo(a)pyrene-induced damages in rat liver microsomes (Devi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It is able to increase both mean and maximum lifespan in C. elegans (Canuelo et al ., 2012) and is well tolerated (Tuck & Hayball, 2002). Tyrosol can afford considerable protection against aging‐associated heart deterioration (Owen et al ., 2000).…”
Section: Identification Of Candidatesmentioning
confidence: 99%